Study on Fatigue Allowance Formulation Based on Physiological Measurements - Li Qu; Juntong Zhang; Di Wang; Lin Zhang; Zhunan Wu (Sensors)
The fatigue allowance effectively mitigates declines in physiological state due to work fatigue. An appropriate allowance rate facilitates timely recovery for employees and serves as a crucial basis for labor quota formulation. In this paper, the action mode in mechanical processing was extracted and disassembled into six action units. The study conducted fatigue measurement experiments based on physiological measurement methods, including exercise fatigue tests at different frequencies and work fatigue tests over varying durations. As the frequency of actions increased, the rate monotonic scheduling index showed a linear increasing trend and the degree of fatigue caused by the action was different. The fatigue coefficient of different action units and the fatigue index of the fatigue instability period were obtained by fitting. Hazard ratio indicators showed significant differences, and the corresponding fatigue recovery rest time was obtained for different continuous operation hours. By further fitting the above data, a fatigue relaxation rate model suitable for simulating operation methods was obtained (the fatigue coefficient for the simulated operations in this study is 0.076152) which could provide a reasonable basis for the formulation of fatigue allowance rates for machining methods.